The Maiden Peak Oestrus - Choudhury, S. R. (Indian Forester, 1977)
The paper deals with field observations on a 21-22 months old tigress (Khairi), during her Maiden Peak Oestrus in Kairakacha camp of Simillpal Tiger Reserve by the Author and his team of Miss Nihar Nalini, Bibhudutta and some Foresters and Forest Guards.'Khairi' the tigress has heen brought up as a pet by the Autbor since infancy. The observations are in the form of a daily diary over a period of 17 days covering the period of the tigress Oestrus. It relates, the daily escapades of the tigress in search of a mate, which later was confirmed to be moving at a distace of nearly 8 km Crom Authors camp. The observations indicate that the tigress was indicating her presence to the mate by scent markings (as is usual with tigress in Oestrus) without any vocalization by either of them. The tgress slso followed the direction of the male tiger more on the basis of smell. The search for a mate was unfruitful due to Author's taking away the tigress from the area for fear of being killed by the villagers if left un-protected. The paper also highlights the behavioural conflict of the tigress between her biological demands and attachment to her foster parents.